Early pregnancy intrauterine fetal exposure to maternal smoking and impact on fetal telomere length. (November 2017) - Mirzakhani, Hooman; De Vivo, Immaculata; Leeder, J. Steven; Gaedigk, Roger; Vyhlidal, Carrie A.; Weiss, Scott T.; Tantisira, Kelan
Abstract: Background: Reduced telomere length, or its accelerated attrition, has been implicated in aging, mortality, and several human diseases, including respiratory diseases. Age dependent manifestation of telomere-mediated disease during life span indicates the role of developmental stage in these diseases and highlights the importance of fetal developmental process in utero and at earlier life stages. Environmental determinants during developmental and later stages of life could affect telomere length. Smoke exposure as one of these significant determinants have been investigated in association with telomere length in neonates at time of delivery, children and adults. Objective: We sought to investigate whether intrauterine fetal exposure to tobacco smoking characterized by placenta cotinine levels during early weeks of pregnancy might be associated with shorter relative telomere length (T/S ratio) as compared to fetuses without exposure to tobacco smoking. Study design: 207 Human placenta and epithelial lung samples were used for both fetal lung telomere length assessment and measurement of placental cotinine levels. Tissues were obtained from two NICHD–supported tissue retrieval programs with registries for elective abortions, the University of Washington Center for Birth Defects Research (Seattle, WA) and the University of Maryland Brain and Tissue Bank for Developmental Disorders (Baltimore, MD). Cotinine levels (ng/g total placental tissue) were determined in whole cell extracts prepared from human placenta samples to characterize and confirm the cotinine exposure status associated with maternal smoking. Relative telomere length (T/S ratio) in genomic DNA extracted from fetal lung tissue was measured by use of quantitative real-time polymerase chain reaction. Multivariable linear regression was used to investigate the relationship between fetal Telomere-to-Single Copy (T/S) ratio and tobacco exposure. Results: The estimated post-conception ages for included samples in the study ranged from 54 to 137 days (7–19 weeks of gestation); 47.37% of fetal samples had female sex. Of the samples included in the analysis 96 and 111 fetal samples with and without intrauterine tobacco smoking exposure were distinguished. While T/S ratio was not different between those with and without smoking exposure (1.24 ± 0.41 and 1.27 ± 0.48, respectively; P = 0.70), a significant effect modification of post-conception age on the relationship of intrauterine smoke exposure on fetal T/S ratio was observed (adjusted coefficient = −0.008, 95% CI: −0.016, −0.0004). The smoke exposure status was associated with T/S ratio after 93-day post conception (adjusted coefficient = −0.29, 95% CI: −0.53, −0.052). Conclusions: Our results demonstrate a significant association of smoke exposure in utero at early pregnancy with shortened fetal relative telomere length in the developing lung and suggest that the detrimental effect of smoking exposure on future disease sequelae may start at the early stages of pregnancy.